Tanta gente sem casa, tanta casa sem gente: o direito ao centro da cidade - Martins, Bianca Camargo (2019)
This dissertation seeks to understand to what extent it is possible to build social housing in central area, focusing on the case of Ponta Grossa - PR. Based on the concept of the right to the city and, consequently, the right to housing, the research analyzes how housing policies allow or do not allow the implementation of housing policies in central areas. The main justifications presented by the government as limiting factors are: land scarcity, real estate speculation and the high price of land. Thus, the possibilities and the limits of urban voids are investigated as a space for social housing. As empirical case studies, we use an existing housing development of the Minha Casa Minha Vida Program - located in an urban expansion area - and a simulation of a project implemented in an urban void in the central area of the Municipality. Both studies are qualitatively explored, based on the location analysis that ascertains the conditions surrounding the projects and their residents' access to the city, and the quantitative analysis, through their implementation costs, from the land acquisition costs up to the costs of running the required infrastructure. By comparing the case studies, the feasibility of social housing in the central areas is proved viable by using urban voids, even in those areas with higher economic value. From the results obtained, it is also shown the incompatibility of the current housing policy with the production of vertical and well located housing.